Writers who love too much new narrative writing 1977-1997 - Bellamy, Dodie ca. 20./21.Jh; Killian, Kevin 1952-2019 (Nightboat Books, 2017)
Machine generated contents note: "Sanchez and Day," from Elements / Robert Gluck -- "The End," from Great Expectations / Kathy Acker -- "Against a Field Sinister" / Edith A. Jenkins -- "Animal Instincts" / Carla Harryman -- "Five Year Plan" / David O. Steinberg -- "Joan," from I Can't Distinguish Opposites / Michael Amnasan -- Interviewed by Steve Abbott and Dodie Bellamy / Judy Grahn -- "A Real Story" / John Norton -- "Wearing a Tough Jacket" / Marsha Campbell -- Interviewed by Steve Abbott / Brad Gooch -- "Satan" / Brad Gooch -- "Lynette #I," "BABY," and "Sex Life" / Camille Roy -- "Jimmy," "Walking to the Ocean This Morning," "Nothing Ever Just Disappears" / Sam D'Allesandro -- Interviewed by Charles Bernstein / Bruce Boone -- "My Mark," from Safe / Dennis Cooper -- From The Double Standard / Kathe Burkhart -- "Scene One," from Decoto / Roberto Bedoya -- "Post War" / F.S. Rosa -- "The Sky Looked Bruised, and That's the Way the Air Felt, Achey" / Robert Gluck
Contributors include: Steve Abbott, Kathy Acker, Michael Amnasan, Roberto Bedoya, Dodie Bellamy, Bruce Benderson, Charles Bernstein, Nayland Blake, Bruce Boone, Lawrence Braithwaite, Rebecca Brown, Kathe Burkhart, Marsha Campbell, Dennis Cooper, Sam D'Allesandro, Gabrielle Daniels, Leslie Dick, Cecilia Dougherty, Bob Flanagan, Robert Glück, Judy Grahn, Brad Gooch, Carla Harryman, Richard Hawkins, Ishmael Houston-Jones, Gary Indiana, Edith A. Jenkins, Kevin Killian, Chris Kraus, R. Zamora Linmark, Eileen Myles, John Norton, F.S. Rosa, Camille Roy, Sarah Schulman, Gail Scott, David O. Steinberg, Lynne Tillman, Matias Viegener, Scott Watson, Laurie Weeks
Includes bibliographical references
Keywords: New narrative (Literary movement); Short stories, American; American fiction / 20th century; American poetry / 20th century; Anthologie